Affection Of Family In Terrence Malick's The Tree Of Life Movie (2011): A Psychoanalytic Approach - Hastuti, Diyah Murti; , Dr. Phil. Dewi Chandraningrum, S.Pd., M.Ed; , Titis Setyabudi, S.S., M.Hum (2013)
The Tree of Life movie directed by Terrence Malick published in 2011.The study is to clarify how the way and the shape of affection in the family are reflected in the movie. The writer proposes to analyze id, ego, superego, affection and family in a film with the title The Tree of Life with Psychoanalytic Approach. There are two objectives of the study. Firstly, it is to analyze film in term of structural elements and secondly is to analyze in term of psychoanalytic approach. The object of this study is The Tree of Life movie directed by Terrence Malick. The writer employs the descriptive qualitative as a type of the research. The data source in this research is divided into two types that are primary data and secondary data. Primary data source is The Tree of Life movie and secondary data source are books or any information related to the practice of affection of family that support the psychoanalytic approach. The method of collecting data is documentation. The technique of analyzing data in this research paper is descriptive. The result of the study comes to the three following conclusions. First, based on structural element in The Tree of Life, it shows that character and characterization, setting, plot, point of view, theme, and cinematography are related to each other and form of unity. Second, based on psychoanalysis analysis, the id, ego, superego, and affection are reflected in each of major character's life. All of them involved in the process of major character searching the existence of God. Third, Mr. O'Brien's family has different expression in showing their affection that can be considered as conceptualization of affection in family.